تحليل كتاب روضة العقلاء و نزهة الفضلاء للإمام الحافظ أبي حاتم محمد بن حبان البستي - suciati suciati (EL- Hayah, 2024)
This article describes the presentation and content of poetry in the books Rawdat al-Aqlaa and Nuzhat al-Fadlaa by Imam al-Hafiz Abu Hatim Muhammad Ibnu Hibban. Researchers used special prosodic studies that did not find rhyme. This research includes the theories of bahr, 'ilat, and zuhaf, and adds 'general' content. The way to use this theory is to analyze the poems in the books Rawdat al-Qalaa and Nuzhat al-Fadlaa. This research is a qualitative descriptive study. The data is in the form of poems from the first to third chapters in the book "Rawdat al-Uqlaa wa Nuzhat al-Fadlaa" by Imam Al-Hafiz Abu Hatim Muhammad Ibnu Hibban, and this book is the main source, while the secondary source is the book Rawdat al-Uqlaa wa Nuzhat al-Fadlaa, translation of his book. The data collection method is the library method, namely by reading and taking notes. There are nine seas used in the first to third chapters of the books Rawdat al-Uqlaa and Nuzhat al-Fadlaa, including: Bahr al-Taweel, Bahr al-Basit, Bahr al-Kamil, Bahr al-Hazj, Bahr al-Raml, Bahr al-Sari'i, Bahr al-Mansarih, and Bahr al-Khafif. And the sea is close by. Each sea has different conditions of presentation and reproduction and can change at any time as well as disease. Its contents: invites you to adhere to reason, the characteristics of a wise and intelligent person, mentions the perfection of secrets through the need to be devout, and states the urgent need for knowledge and diligent search.